Reducing Material Loss in Gold Bracelet Production Using Material Flow Cost Accounting and Value Stream Mapping - Andreas Dhiyong Pratama; Lukmandono Lukmandono; Gatot Basuki Hari Mukti (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2026)
Material loss is a critical issue in gold jewelry manufacturing because it increases production costs and reduces resource utilization efficiency. This study aims to identify material loss and its associated costs using Material Flow Cost Accounting (MFCA), analyze production waste through Value Stream Mapping (VSM), determine the root causes of inefficiencies using a Fishbone Diagram, and develop improvement strategies based on the 5W+1H approach. A quantitative descriptive method was employed using production data from the Morena 12K bracelet manufacturing process at PT XYZ during the period of Desember 2025 to February 2026. MFCA was applied to quantify material flow and classify production costs into positive and negative costs, while Current State Value Stream Mapping (CSVSM) was used to identify value-added and non-value-added activities. The results indicated that material loss fluctuated between 10.39% and 23.06%, resulting in negative costs ranging from IDR 1.07 billion to IDR 2.89 billion. Waste analysis revealed that waiting and defect were the dominant sources of inefficiency, primarily caused by machine downtime, CNC setup, and finishing operations. The proposed improvements, developed using the 5W+1H approach and evaluated through Future State Value Stream Mapping (FSVSM), reduced production lead time from 421.417 minutes to 381.967 minutes and increased Process Cycle Efficiency (PCE) from 35.29% to 42.71%. Furthermore, the Future MFCA evaluation demonstrated a reduction in negative costs and material loss, accompanied by an increase in positive costs, indicating more efficient material utilization and improved production performance. These findings demonstrate that integrating MFCA and VSM is an effective approach to minimizing material loss, reducing hidden production costs, and supporting continuous improvement in gold jewelry manufacturing.